The Effect Of Auxin Concentration (Rootone F) And The Application Of Lamtoro (Leucaena Leucocephala) Leaf POC On The Growth Of Robusta Coffee (Coffea Canephora) Seedlings - Fajar Setiawan; Andi Setiawan; Kabul Warsito (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to determine the effect of auxin concentration (Rootone-F) and liquid organic fertilizer (POC) from lamtoro leaves (Leucaena leucocephala) on the growth of robusta coffee seedlings (Coffea canephora). The study was conducted in March–May 2025 in Sampe Cita Village, Kutalimbaru District, Deli Serdang Regency, North Sumatra. The research method used a factorial Randomized Block Design (RAK) with two factors, namely the concentration of lamtoro leaf POC (M0=0 ml, M1=200 ml, M2=250 ml, M3=300 ml) and the concentration of Rootone-F (A0=0 ml, A1=200 ml, A2=250 ml, A3=300 ml), with three replications. The parameters observed included plant height, leaf area, number of leaves, and root length. The results showed that the administration of lamtoro leaf POC and Rootone-F significantly affected plant height, leaf area, and number of leaves of robusta coffee seedlings. The best treatment was obtained with a combination of 300 ml of lamtoro leaf POC and 250 ml of Rootone-F which resulted in optimal vegetative growth. Increasing the concentration of Rootone-F tended to decrease root length due to the biphasic effect of auxin on root growth. It can be concluded that the use of lamtoro leaf POC and Rootone-F at the right dosage can significantly increase the growth of robusta coffee seedlings.